2009
DOI: 10.3174/ajnr.a1742
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Study of the Cortical Origin and Course of the Corticospinal Tract in Healthy Children

Abstract: BACKGROUND AND PURPOSE Several studies have questioned the traditional belief that the corticospinal tract (CST) arises exclusively from the precentral gyrus and passes through the anterior half of the posterior limb of the internal capsule (PLIC) in humans; however, no direct evidence existed from structural imaging, and developmental aspects of CST origin have not been clarified. We used diffusion tensor imaging (DTI) tractography to test the hypotheses that CST can originate from both pre- and postcentral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
3
41
0
2
Order By: Relevance
“…As a result, they reported that 60% of the CST originated from the precentral gyrus. Kumar et al in 2009 17 recently reported on the origin of the CST by using diffusion tensor tractography. DTI was performed in 42 healthy children (2.6 -12.7 years of age).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, they reported that 60% of the CST originated from the precentral gyrus. Kumar et al in 2009 17 recently reported on the origin of the CST by using diffusion tensor tractography. DTI was performed in 42 healthy children (2.6 -12.7 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…10,[33][34][35] Several previous studies have reported the distribution of the CST origin in the cerebral cortex in primates. 11,12,14,17 In 1961,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations